PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI PUSAT PENYULUHAN PERTANIAN KEMENTERIAN PERTANIAN - Nada Rahmah Dani Kaltsum (2021)
This research is a quantitative study that aims to determine and prove whether there is an influence between job satisfaction and work discipline on employee performance at the Agricultural Extension Center, Ministry of Agriculture. In this study, the sample used was 70 people, the sampling technique used was saturated sampling technique. In this research hypothesis, namely to determine the effect either partially or simultaneously of variables X and Y, so that the tests used are the coefficient of determination test, f test and t test. Furthermore, the research results obtained are: (1) job satisfaction has a positive and significant influence on employee performance, (2) work discipline has a positive and significant effect on employee performance, (3) job satisfaction and work discipline have a positive influence. and significantly with the performance of employees at the Agricultural Extension Center